Measuring the Intellectual Capital of International Carriers as Logistic Operators - Zebec, Sabina; Zelenika, Ratko; Zečević, Slobodan (Promet - Traffic&Transportation, 2007)
The age of knowledge has come and the enterprises presentthemselves as »knowledge ente1prises<< and their employees assources of knowledge - »knowledge workers«. Knowledge hasbecome a merchandise, to be on the knowledge market. In anenterprise knowledge becomes the capital, important forachieving competitive advantage on the market but it cannot bemeasured easily. The field of intellectual capital is ve1y complex,mostly because it is difficult to categorize it. The importantconcepts and definitions for intellectual capital include an emphasisthat intellectual capital is based on knowledge and is usablein any enterprise. Knowledge and skills determine the possibilitiesof an individual to actively influence the social developmentand ensure their quality of life.